Inner and Outer Retinal Contributions to Pupillary Light Response: Correlation to Functional and Morphological Parameters in Glaucoma (2018)
Purpose: To evaluate in patients with Primary Open Angle Glaucoma (POAG) the contribution of the inner and outer retinal photoreceptors to the pupillary light responses (PLRs) correlated with both functional (color vision and visual field (VF) perimetry) and morphological (optical coherence tomography-OCT) parameters. Methods: Forty-five patients with POAG and 25 healthy control participants were evaluated. The PLR was measured as pupil diameter with an eye tracker; stimuli were presented in a Ganzfeld. Pupil responses were measured monocularly, to 1 seconds blue (470?nm) and red (640?nm) flashes with ?3, ?2, ?1, 0, 1, 2, and 2.4?log cd/m2 luminance levels. Color vision was evaluated with the Cambridge Colour Test (CCT), VF was measured by standard automatic perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness was evaluated by OCT. Results: Patients with moderate and severe POAG have a significantly decreased PLR that depends on the severity of POAG, for both the 470 and 640?nm stimuli, revealing the reduction of the contributions of the rods, cones and intrinsically photosensitive retinal ganglion cells (ipRGCs) to PLR. A significant loss of color discrimination along the blue-yellow axis was observed in all stages of POAG. Correlations among SAP, RNFL thickness, CCT, PLR and melanopsin parameters were found. Conclusions: The results provide evidence that in moderate and severe stages of POAG, both the inner and outer retinal contributions to PLR are affected. Also, a worsening in color vision was correlated with reduced PLR responses at high-intensity stimuli. These findings may enhance the clinical management of POAG patients. Copyright © 2018 Wolters Kluwer Health, Inc. All rights reserved.